Evaluasi Pengalaman Pengguna menggunakan Metode UX Honeycomb pada Aplikasi Pengenalan Wadai Banjar berbasis Augmented Reality - Subandi Subandi; Aulia Akhrian Syahidi; Ahmad Zairullah Redhani; Akhmad Sayuti (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
One of the tourist attractions in South Kalimantan Province is the existence of a variety of typical cakes or often referred to as Wadai Banjar. Wadai Banjar has various types and usually, visitors will have culinary delights, so through an application called AR-WadaiBanjar based on Augmented Reality (AR) technology that has been built, it is recommended to introduce various types of Wadai Banjar such as names, prices, seller shop recommendations, along with the recipe for making the Wadai Banjar. The purpose of this study is to evaluate the user experience of the AR-WadaiBanjar application that has been used by users. The method used is UX Honeycomb, which has seven aspects to assess the user experience of an application. A total of 100 users who were respondents were presented to assess the user experience of the application. The results showed that the AR-WadaiBanjar application had an average Honeycomb UX value of 4.49 with the predicate Agree. This means that the AR-WadaiBanjar application has met the user experience aspect in the Good category. However, some improvements are needed for the shortcomings of the application by improving the type of text in the user interface, the need for a map to indicate the location of the cake shop, improving the user experience, and other smart capabilities.